2013
DOI: 10.1002/aenm.201300308
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance and Stability of Inverted Organic Solar Cells with Sol–Gel Processed, Amorphous Mixed Metal Oxide Electron Extraction Layers Comprising Alkaline Earth Metals

Abstract: Stability of organic photovoltaic devices (OPVs) is a limiting factor for their commercialization and still remains a major challenge whilst power conversion efficiencies are now approaching minimum requirements. The inverted organic solar cell (iOSC) architecture shows promising potential for improving significantly the cell's working lifetime. However, when solution processed ZnO is used as electron extraction layer, an undesirable light‐soaking step is commonly required before the device reaches a non‐perma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 59 publications
8
62
0
Order By: Relevance
“…Again, we want to confi rm that these fi ndings are in agreement with the formation of a O A bond, reducing the otherwise oxygen and humidity susceptible dangling bonds. [ 38,41 ] Therefore, no obvious "light-soaking" is observed in devices with alkali hydroxide/metal oxides ETLs. We anticipate that the fi nal OSC product will not rely on UV light treatment due to the interface treatment by solution-processed alkali hydroxides.…”
Section: Wileyonlinelibrarycommentioning
confidence: 97%
“…Again, we want to confi rm that these fi ndings are in agreement with the formation of a O A bond, reducing the otherwise oxygen and humidity susceptible dangling bonds. [ 38,41 ] Therefore, no obvious "light-soaking" is observed in devices with alkali hydroxide/metal oxides ETLs. We anticipate that the fi nal OSC product will not rely on UV light treatment due to the interface treatment by solution-processed alkali hydroxides.…”
Section: Wileyonlinelibrarycommentioning
confidence: 97%
“…Besides aluminium and the group III elements, the group-II elements (alkaline earth), such as magnesium (Mg), strontium (Sr) and barium (Ba) doped ZnO ( named as MZO, ZnSrO and ZnBaO, respectively) layers also have been introduced into inverted PSCs. 48,202 Besides the metals, the fullerene derivatives have been used to dope ZnO for forming an efficient CBL in inverted PSCs. 49,114 The photovoltaic performance of inverted devices based on these doped ZnO CBLs in literature is summarized in Table 2.…”
Section: Doping Of Zno Cbls In Inverted Polymer Solar Cellsmentioning
confidence: 99%
“…48,202 Pachoumi et al reported an improved performance and stability of inverted PSCs by employing the sol-gel processed amorphous Sr and Ba doped ZnO CBLs prepared at relatively low temperature. 202 The inverted PSCs based on Sr and Ba doped ZnO CBLs exhibited higher performance and better stability than the devices with pure ZnO CBLs. In addition, the commonly requirement of light soaking for reaching a maximum photovoltaic performance of inverted device based on i-ZnO CBLs was successfully circumvented.…”
Section: Doping Of Zno Cbls In Inverted Polymer Solar Cellsmentioning
confidence: 99%
“…Additionally, the localized O 2p based valence bands, which are typically deep and poorly dispersed, should block hole injection from typical organic donor HOMOs (43). Although compositional investigations on amorphous oxides have been reported in Zn 1-x Ba x O, Zn 1-x Sr x O, and Ga 1-x Zn x O systems (44,45), systematic band alignment tuning via doping such oxides has not been demonstrated.…”
Section: Significancementioning
confidence: 99%